2020
DOI: 10.3390/en13020468
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of CH4 to C2 Hydrocarbons in a Packed Bed DBD Plasma Reactor: The Effect of Dielectric Constant and Porosity of the Packing

Abstract: The conversion of methane was investigated in a packed-bed dielectric barrier discharge (DBD) plasma reactor operated at ambient conditions. High dielectric BaTiO3 was utilized as packing in comparison with γ-alumina, α-alumina, and silica-SBA-15. Results show a considerably lower conversion of CH4 and C2 yield for the BaTiO3 packed reactor, which is even less than that obtained for the nonpacked reactor. In contrast, the low dielectric alumina (γ and α) packed reactor improved the conversion of CH4 and C2 yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 30 publications
2
18
1
Order By: Relevance
“…Thus, a presence of the packing material inside the reactor generally decreases the discharge power under the same operating conditions. These findings are in agreement with the results of other authors, who also observed the same effect [49][50][51]. Inserting the packing material into a discharge gap has an influence on discharge mode [52,53], when the filamentary discharge mode typical for non-packed DBD reactors may change into surface discharge mode or into their combination [54].…”
Section: Discharge Characteristicssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, a presence of the packing material inside the reactor generally decreases the discharge power under the same operating conditions. These findings are in agreement with the results of other authors, who also observed the same effect [49][50][51]. Inserting the packing material into a discharge gap has an influence on discharge mode [52,53], when the filamentary discharge mode typical for non-packed DBD reactors may change into surface discharge mode or into their combination [54].…”
Section: Discharge Characteristicssupporting
confidence: 92%
“…Such change in discharge mode can also occur with the increasing of the applied voltage [55]. Furthermore, each pellet of packing material functions as a capacitor, so the charges can be trapped rather than being transferred across the gap, which also may affect the discharge current and its mode [49]. Thus, all these effects have an impact on the discharge properties including power consumption.…”
Section: Discharge Characteristicsmentioning
confidence: 99%
“…A higher voltage of 8.8-9.0 kV is required when the plasma gap is packed with the catalyst, in comparison with the value of the voltage applied for the non-packed reactor (7.6 kV), in order to obtain the same value, of 7-8 W, as the output power. Furthermore, the breakdown voltage (i.e., obtained from the Lissajous Figures, depicted in Figure 1 changes as the discharge gap is filled by catalyst particles, lowering the space for the propagation of plasma discharges [19][20][21]. Figure 1 depicts the Lissajous Figures for the blank reactor and the packed reactor with γ-alumina and Pd-loaded γ-alumina.…”
Section: The Plasma Electrical Parametersmentioning
confidence: 99%
“…For a SEI below 4 kJ/L, the conversion of methane for the packed reactor is lower than that in the blank reactor. The reason is attributed to the presence of the catalyst and its impact on the formation of discharges, which is called the "partial discharging" [21][22][23], occurring in packed bed DBD reactors. In addition, the energy provided at low SEIs is not sufficient to propagate the discharges across the catalyst bed.…”
Section: The Effect Of Specific Energy Input (Sei)mentioning
confidence: 99%
See 1 more Smart Citation